2022
DOI: 10.3389/fpls.2022.814255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Warming and Phosphorus Enrichment on the C:N:P Stoichiometry of Potamogeton crispus Organs

Abstract: The loss of submerged macrophytes from freshwater ecosystems is accelerating owing to the combined effects of eutrophication and climate change. Submerged macrophytes depend on spring clear water; however, increased water temperatures and excessive phosphorus (P) inputs often lead to the dominance of phytoplankton. It is still not clear how the stoichiometric characteristics of carbon (C), nitrogen (N), and P in different tissues of submerged macrophytes respond to P enrichment and temperature increases. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
(86 reference statements)
1
0
0
Order By: Relevance
“…Previous studies have shown that the contents of C, N and P in plants are often different under different utilization patterns or at different growth stages [26][27][28][29][30]. In this study, the plant C content was highest in EG and lowest in MG, showing EG > GG > MG. N and P are important components that affect the synthesis of proteins, nucleic acids, enzymes and other important compounds in plants, and they also affect all physiological activities of a plant's life cycle [27].…”
Section: Plant C N and P Content And Stoichiometric Ratiosupporting
confidence: 45%
“…Previous studies have shown that the contents of C, N and P in plants are often different under different utilization patterns or at different growth stages [26][27][28][29][30]. In this study, the plant C content was highest in EG and lowest in MG, showing EG > GG > MG. N and P are important components that affect the synthesis of proteins, nucleic acids, enzymes and other important compounds in plants, and they also affect all physiological activities of a plant's life cycle [27].…”
Section: Plant C N and P Content And Stoichiometric Ratiosupporting
confidence: 45%